Odpowiedź:
a) f(x) = 2x + 3
2x + 3 = 0
2x = -3
x = -[tex]\frac{3}{2}[/tex] = -1[tex]\frac{1}{2}[/tex]
b) f(x) = x² + 2
x² + 2 = 0
x² = -2
Brak miejsc zerowych, bo x² ≥ 0
c) f(x) = [tex]\frac{x}{2}[/tex] + [tex]\frac{1}{3}[/tex]
[tex]\frac{x}{2}[/tex] + [tex]\frac{1}{3}[/tex] = 0 |×6
3x + 2 = 0
3x = -2
x = -[tex]\frac{2}{3}[/tex]
d) f(x) = [tex]\frac{x^{2} -1}{x+1}[/tex]
Dziedzina: x + 1 ≠ 0
x ≠ -1
D: x∈R - {-1}
[tex]\frac{x^{2} -1}{x+1}[/tex] = 0
x² - 1 = 0
x² = 1
x = 1 ∨ x = -1 (nie może być -1, bo x∉{-1})
Z tego wynika, że:
Miejsce zerowe: x = 1